Galaxy populations in the Antlia cluster : II. Compact elliptical galaxy candidates - Smith Castelli, Analía Viviana (2008)
We present a photometric analysis of four galaxies classified as compact elliptical (cE) galaxies in the FS90 Antlia Group catalogue. Only 6 members of this rare type of galaxies are known until now. Using data in various photometric systems, we measured brightness and colour profiles, as well as structural parameters. By comparing them with those of other galaxies in the Antlia cluster, as well as with confirmed cE galaxies from the literature, we found that two of the FS90 cE candidates, albeit being spectroscopically confirmed Antlia members, are not cE galaxies. However, one of these objects presents strong ellipticity and position angle variations that resemble those already reported for M32, leading us to speculate about this kind of objects being progenitors of cE galaxies. The other two FS90 cE candidates, for which radial velocities are not available, match some features typical of cE galaxies like being close in projection to a larger galaxy, displaying flat colour profiles, and having a high degree of compactness. Only one of the remaining cE candidates shows a high central surface brightness, two components in its brightness profile, distinct changes in ellipticity and position angle where the outer component begins to dominate, and seems to follow the same trend as other confirmed cE galaxies in a luminosity versus mean effective surface brightness diagram. Moreover, it shows a distorted inner structure with similar characteristics to those found by simulations of interacting galaxies, and an extremely faint structure that seems to link this object with one of the Antlia dominant galaxies, has been detected in MOSAIC-CTIO, FORS1-VLT, and ACS-HST images. The cE nature of this galaxy as well as the possible interaction with its bright companion, still have to be confirmed through spectroscopy.